Konflik Diskursif Netizen Terkait Tragedi Jatuhnya Juliana Marins di Gunung Rinjani di Kolom Komentar Akun Instagram @sar_nasional - Duhri, Moh Khodiq; Hastjarjo, Sri; Anshori, Mahfud (Jurnal Audiens, 2025)
The tragedy of a Brazilian tourist’s fall on Mount Rinjani in June 2025 triggered discursive conflict in the comment section of Instagram account @sar_nasional, shifting the space from sympathy to a site of narrative clashes between Indonesian and Brazilian netizens. This qualitative case study examines how the two groups constructed competing narratives by analyzing 56 relevant comments using Framing Theory and Symbolic Interactionism. Brazilian netizens framed the incident as “systemic negligence” by highlighting delayed response and infrastructural weaknesses, while Indonesian netizens countered with a frame of “volunteer heroism in extreme terrain,” emphasizing geographical challenges and the dedication of SAR teams. The interactions did not evolve into dialogue but instead functioned as rituals of identity affirmation that deepened polarization. This study demonstrates how a humanitarian tragedy can transform into a cross-national narrative conflict at the grassroots level. Practically, the findings underscore the need for rescue institutions to apply crisis management strategies grounded in cross-language communication to prevent escalation, and to develop digital “micro-diplomacy” practices through rapid clarification, contextual explanations, and empathic responses to ease tensions in digital platform comment spaces.